Synthesis and Characterization of Fe3O4 Nanoparticles Modified with Polyethylene Glycol as Antibacterial Material - Poedji Loekitowati Hariani; Desnelli Desnelli; Fatma Fatma; Rizki Indah Putri; Salni Salni (The Journal of Pure and Applied Chemistry Research, 2018)
The iron oxide (Fe3O4) nanoparticles modified with polyethylene glycol (PEG) was synthesized by co-precipitation methods using ferric and ferrous ions as the precursors. Further, the antibacterial activity was performed against gram-positive and gram-negative bacteria. The Fe3O4-PEG was characterized using X-Ray Diffraction (XRD), Fourier Transform Infra Red (FTIR), Scanning Electron Microscopy (SEM) with energy dispersive X-Ray analysis (EDAX) and Vibrating Sample Magnetometer (VSM). The particle size of Fe3O4-PEG calculated using XRD is 46.2 nm. The study confirmed that Fe3O4-PEG is superparamagnetic and has a saturation magnetization of 56.43 emu/g. The prepared Fe3O4-PEG gives the effect of both gram-positive and gram-negative pathogenic bacterial strains hence this material has potential utilization in the field of pharmaceutical and biomedical in the future.